A low-cost digital coding metasurface applying modified 'crusades-like' cell topologies for broadband RCS reduction. (1st December 2022) - Wang, Chao; Wang, Ru-Zhi; An, Ze-Lin; Liu, Li-Ying; Zhou, Yun-Sheng; Tang, Zhi-Xiang; Wang, Wei-Dong; Zhang, Sheng-Jun
Abstract: The popularity of metasurfaces (MSs) has been continuously grown due to their powerful ability to manipulate electromagnetic waves. One of their important application areas is radar stealth technology, in particular, the realization of radar cross section (RCS) reduction. However, the high costs of substrate material limit its large-scale applications. In this paper, a binary digital coding metasurface (DCM) with novel modified 'crusades-like' cell topologies is proposed and implemented using a low-cost FR4 substrate to achieve broadband RCS reduction (RCSR). To realize the 1-bit DCM, initially, two elements with rotational symmetry are chosen for polarization insensitive properties while considering an unconventional phase deviation criteria. Next, the optimal hybrid coding layout is given out by using a genetic algorithm and antenna array theory. Last, the proposed novel MS prototype composed of 40 × 40 unit cells is fabricated and measured to validate the RCSR behaviour predicted by full-wave simulation. The results show a good consistency between the theoretical simulation and experimental measurement from 7.9 to 15.8 GHz. In addition, the simulation results indicate that the designed MS features high angular stability. Our work may provide a promising approach and good reference for the low-cost MS design in radar stealth applications.